2011
DOI: 10.1109/tcsi.2010.2055291
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Analysis of Deep-Submicrometer CMOS Process for Reliable Circuits Designs

Abstract: Abstract-A time-domain methodology for statistical simulation of nonlinear dynamic integrated circuits with arbitrary excitations is presented. The statistical behavior of the circuits is described as a set of stochastic differential equations rather than estimated by a population of realizations and Gaussian closure approximations are introduced to obtain a closed form of moment equations. Statistical simulation of specific circuits shows that the proposed numerical methods offer accurate and efficient soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It should be mentioned here that (71) and (72) have been derived by keeping in mind that both η(t) and κ(t) employ zero mean. By using (70)-(72), we have found that R I1,I2 (t) = R x1,x2 [7,7] and R I1,I2 (t) = R x1,x2 for the on-chip and off-chip transformer respectively. In addition, all expectation operator termed elements of R x1,x2 can be analytically given in terms of the correlation coefficients.…”
Section: The Vector Sdes Of a Trans-former Their Solutions And The Smentioning
confidence: 99%
See 3 more Smart Citations
“…It should be mentioned here that (71) and (72) have been derived by keeping in mind that both η(t) and κ(t) employ zero mean. By using (70)-(72), we have found that R I1,I2 (t) = R x1,x2 [7,7] and R I1,I2 (t) = R x1,x2 for the on-chip and off-chip transformer respectively. In addition, all expectation operator termed elements of R x1,x2 can be analytically given in terms of the correlation coefficients.…”
Section: The Vector Sdes Of a Trans-former Their Solutions And The Smentioning
confidence: 99%
“…Since the variance of any random variable can be given by its mean square subtracted by the square of its mean, the variances of I 1 (t) and I 2 (t) of the on-chip transformer are respectively equal to V 1 [7,7] and V 2 [7,7].…”
Section: The Vector Sdes Of a Trans-former Their Solutions And The Smentioning
confidence: 99%
See 2 more Smart Citations
“…13 As for electrical engineering, the SDE approach has been mostly used to solve noisy issues in electronic circuits with lumped parameters, including monolithic integrated circuits. 411 The present paper applies SDE theory to networks with distributed parameters, and transmission lines (TL) in particular, which are very often utilized for high-speed data transmission. 12–14 To catch effects of random variations of system parameters, standard methods like Monte Carlo are commonly utilized.…”
Section: Introductionmentioning
confidence: 99%